Simulation of synbiotic ice cream fermentation process - M. A. Vavilova (Новые технологии, 2021)
Expanding the range of products of therapeutic and prophylactic orientation is a priority direction of the state policy in the field of healthy nutrition. Products enriched with functional components improve the general state of the body, have high organoleptic characteristics in combination with increased biological value. The production of synbiotic ice cream is one of the promising trends in the dairy industry. Due to its unique composition and technological peculiarities, the ice cream retains the desired organoleptic and functional properties. Pro- and prebiotic components in it are conserved by freezing, and activated only when they enter the organism. It has been established experimentally, that high concentrations of monosaccharides have an inhibitory effect on the development of probiotic cultures, therefore, the purpose of the research is to simulate the fermentation process of the ice cream enriched with prebiotic components, in order to determine optimal characteristics and establish rational syrup concentrations. Lactic bacteria of Lactobacillus acidophilus species that remain active in a wide temperature range and suppressing pathogenic microflora, as well as berry syrup with a high concentration of vitamins and minerals have been used as components that ensure the functionality of the product. Phased addition of syrup has been recommended for the ex- periment. As a result of the research, a model recipe for synbiotic ice cream has been developed, the quantitative regularities of the influence of various concentrations of fructose syrup on the process of fermentation of compound have been determined, organoleptic characteristics of soft-serve ice cream have been investigated, a power-law model of the dependence of the duration of fermentation on the mass fraction of fructose syrup has been obtained. It has been found that a decrease in the initial concentration makes it possible to shorten the technological cycle and regulate the acidity index.